PENGARUH PENGETAHUAN KEWIRAUSAHAAN, LINGKUNGAN KELUARGA DAN LOCUS OF CONTROL TERHADAP MINAT BERWIRAUSAHA MAHASISWA AKUNTANSI - Eny Suprapti; Minsar Muhammad (J-MACC, 2022)
A This study aims to determine the effect of entrepreneurial knowledge, family environment and locus of control on entrepreneurial interest in accounting students at STIE Wira Bhakti Makassar which provides an initial picture of the percentage of graduates absorbed in the world of work or creating jobs. Using quantitative methods with primary data and questionnaires. The measuring instrument consists of 9 question items for entrepreneurial knowledge, family environment and interest in entrepreneurship and 13 question items for locus of control. Based on the partial statistical test, taking into account the t-count comparison that is larger than the table and the significance level is smaller than 0.8% from the standard significance of 5%, it can be concluded that Ho is rejected or the locus of control partially has a significant effect on entrepreneurial interest. The results of the first hypothesis regression test concluded that entrepreneurial knowledge has a significant influence on acceptable entrepreneurship interest. The results of the second and third hypothesis regression tests concluded that theoretically and statistically, family environment and locus of control have a significant influence on entrepreneurial interest.